Epidermal Growth Factor Receptor Expression and Mutations as Diagnostic and Predictive Biomarkers in Lung Cancer: A Literature Review - Sri Melati Munir; Wirsma Arief Harahap; Masrul Basyar; Noza Hilbertina (Jurnal Kesehatan Komunitas Indonesia, 2026)
Lung cancer remains a leading cause of cancer-related mortality worldwide, with diagnostic challenges due to nonspecific symptoms and limitations in tissue sampling. Molecular biomarkers, particularly Epidermal Growth Factor Receptor (EGFR), have gained attention for improving diagnostic accuracy and understanding tumor biology. EGFR plays a critical role in regulating cell proliferation, differentiation, and survival through multiple signaling pathways. This study aims to analyze the role of EGFR expression as a diagnostic biomarker in lung cancer by reviewing its biological function, molecular mechanisms, and clinical relevance. This study used a literature review approach by collecting relevant articles from databases such as PubMed, Scopus, and Google Scholar. Keywords including “EGFR,” “lung cancer,” and “biomarker” were used to identify studies discussing EGFR expression and its diagnostic value. EGFR overexpression and mutations are frequently found in lung cancer, especially non-small cell lung cancer. Activation of EGFR triggers signaling pathways such as MAPK, PI3K, and STAT, promoting tumor proliferation and survival. Detection methods, including immunohistochemistry, PCR, and FISH, are widely used. EGFR expression has shown potential as a diagnostic biomarker and provides important information for targeted therapy. EGFR expression plays a significant role in lung cancer diagnosis and offers potential as a diagnostic biomarker. However, variations across populations and tumor subtypes require careful interpretation in clinical applications.